An Empirical Study of the Effects of Demographic Factors on Economic Growth in Advanced and Developing Countries - Serhii Kozlovskyi; Mykola Pasichnyi; Ruslan Lavrov; Natalya Ivanyuta; Anton Nepytaliuk (Comparative Economic Research. Central and Eastern Europe, 2020)
In this article, an updated approach to investigate the effects of demographic fac- tors on economic growth is proposed. The initial hypothesis was that these factors significantly affected production proportions, determining development vectors. The predictable shifts in production dynamics are considered for the institutional frame- work. The article investigates the statistically significant relationships between the demographic variables and economic growth for the sample of the OECD countries (excluding Columbia) and Armenia, Belarus, Bulgaria, Croatia, Georgia, Kazakhstan, Romania, the Russian Federation, and Ukraine, from 1990 to 2017; unbalanced panel data was used. The investigation aimed to highlight the intrinsic interconnection between the changes in demographic variables (e.g., the working-age population growth rate and the average life expectancy growth rate) and economic growth. Our investigation focused on the issue of whether demographic influence on economics was the same for advanced and developing countries in the sample. Over the period, a significant increase in life expectancy adversely affected the real GDP per cap- ita growth rate. However, the empirical study pointed out that life expectancy was strongly linked to nominal GDP per capita. In advanced countries, the demographic indicator was considerably higher than in emerging markets. We found that the rise in the working-age stratum of the nation's population radically reduced the output dynamics as well, but that interconnection was not robust. The institutional framework should be taken into account in order to achieve a favorable performance of public governance in the long-run. The main demographic variables should be properly forecasted and calibrated for potential endogenous economic triggers. Both public and private investments are important when considering the economic growth rates that are achieved. We propose a balanced approach to macroeconomic policy regarding both demographic and institutional determinants.
Keywords: E22; I30; J10; J18; J24; O10; 330; population; human capital; demographic sustainability; institutionalframework; economic growth; Bevölkerungsentwicklung; Bevölkerungsstruktur; Humankapital; Wirtschaftswachstum; Bevölkerungsökonomik; Vergleich; OECD-Staaten; Entwicklungsländer